DEVELOPMENT OF ANIMATION VIDEOS TO IMPROVE THE ENVIRONMENTALLY CARING CHARACTER OF ELEMENTARY SCHOOL STUDENTS - Aan Yuliyanto; Amar Jihad Joyalwi; Candra Tri Utami; Tia Citra Bayuni; Julia Anis Handayani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to provide an overview of animated videos that can improve the environmental awareness of elementary school students through the development of an animated video framework and a literature review. The instruments used were an elementary school student response questionnaire and an expert validation sheet. This article only discusses the process of developing animated videos and the results of the literature review. Video is an audiovisual medium that combines moving images accompanied by audio with animated characters, which can help students more easily grasp the material so that students will be interested and focused on following the learning process related to environmental care with direct examples on the show. Animated videos are made. Thus, animated videos are considered suitable for improving the environmental awareness character of elementary school students. The findings in this study can be used as a solution that animated videos can provide new experiences, attract students' attention, and make the learning process easier to understand and more meaningful, especially in instilling a character of caring for the environment. The novelty and implications of this research are that animated videos with the theme of caring for the environment using the Animaker application can provide new experiences for students, about the importance of maintaining environmental cleanliness combined with learning videos that attract students' attention so that the learning process is more enjoyable. Animation can also help students remember material from images longer. Displaying images can help students understand the material presented more clearly